2020
DOI: 10.1111/jop.13096
|View full text |Cite
|
Sign up to set email alerts
|

Expression and methylation of Dickkopf‐1 in the pathogenesis and malignant transformation of oral submucous fibrosis

Abstract: Background Dickkopf‐1 is an inhibitor of the Wnt/β‐catenin pathway, but the role of Dickkopf‐1 in oral submucous fibrosis remains unclear. We evaluated the protein expression and gene methylation levels of dickkopf‐1 to determine the mechanism underlying abnormal Wnt/β‐catenin pathway activation. Methods Healthy mucosa, oral submucous fibrosis, oral squamous cell carcinoma, and cancer‐adjacent tissues were collected. The expression and promoter methylation levels of dickkopf‐1 were analyzed. Results The expres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 25 publications
0
12
0
Order By: Relevance
“…of positive cells/No. of cells) × 100 [29], and H-score is calculated as 1 × (% of 1 + cells) + 2 × (% of 2 + cells) + 3 × (% of 3 + cells) [30].…”
Section: Data Extractionmentioning
confidence: 99%
See 4 more Smart Citations
“…of positive cells/No. of cells) × 100 [29], and H-score is calculated as 1 × (% of 1 + cells) + 2 × (% of 2 + cells) + 3 × (% of 3 + cells) [30].…”
Section: Data Extractionmentioning
confidence: 99%
“…Further comprehensive evaluation against the inclusion criteria excluded 32 articles. The total of 14 articles were included in the systematic review [20][21][22][23][24][25][26][27]29,30,[33][34][35][36], as shown in Figure 1.…”
Section: Study Selectionmentioning
confidence: 99%
See 3 more Smart Citations